THE ANALYSIS OF SYNTACTICAL INTERFERENCE IN ENGLISH PHRASES IN STUDENTS’ WRITING : (A Descriptive Study at the Second Grade Students of SMP 2 Kuta Baro, Aceh Besar) - Salwa Chaira; Diana Topan (Getsempena English Education Journal, 2017)
This qualitative-descriptive research attempts to describe Indonesian interference in building English phrases in writing. The research was undertaken to the second year students of SMP 2 Kuta Baro, Aceh Besar. This study aims to verify the Indonesian interference made by students in English phrases. The data were collected through document analysis which then the sample was selected to be analyzed. The sample of this study was twelve narrative texts composed by the students. The finding of data analysis reveals that there are some syntactical interference samples made by them as in scenery roads, voice strange, morning Sunday, water bath, garden flower, and advice future. These are resulted from Indonesian interference because they applied Indonesian structure in building English phrases. In conclusion, the research result shows that the students have lack of grammar knowledge in constructing English phrases. Therefore, they borrow Indonesian structure as a solution for their difficulties. For this reason, the teaching should focus more on how to build English phrases correctly by giving many samples of nounʸ + nounˣ (where nounˣ means head and nounʸ means modifier) pattern all well as explaining the rule in English as the target language they are learning. It hopes that they will not transfer the Indonesian pattern when they are writing in English.